16S RRNA ANALYSIS OF MICROBIOTA COMPOSITION AGAINST THE BACKGROUND OF SARS-COV-2 INFECTION USING MOLECULAR DIAGNOSTICS (LITERATURE REVIEW) - Sobirjon T. Jumamurodov; Zukhra A. Nuruzova (Central Asian Journal of Medicine, 2025)
This article is devoted to the study of microbial environmental changes against the background of SARS-CoV-2 infection using molecular diagnostics. The composition of the human microbiota was analyzed using 16S rRNA sequencing technology and the dysbiosis of the microbiota associated with COVID-19 was studied. The article presents scientific data on the enrichment or reduction of the microbiota with different categories of microorganisms during SARS-CoV-2 infection, as well as their impact on health and the immune system. The clinical implications of changes in the structure of the microbiota and the possibility of their application for diagnostic purposes have also been considered.